The Nature of Gentrification. Issue 8 (2nd August 2013) - Bryson, Jeremy
Abstract: Gentrification research provides many important insights into the transformation of contemporary urban landscapes, yet more careful attention to nature's role in this process is necessary. This essay begins by highlighting how gentrification research has traditionally overlooked the environmental factors of gentrification and continues by showing how researchers are beginning to account for the urban natural environment in gentrification processes. Such an environmentally sensitive approach to gentrification—one that accounts for nature being used by powerful groups as a tool of social power but also leaves room for it to be a dynamic material actor—can aid scholars' understanding of this important urban process.